Development of an Extruded Food Product Similar to Fried Potatoes, Based on By-Products of Potatoes and Rice. Physicochemical and Microbiological Evaluation - Roman-Miranda, J; Almendares-Calderon, L; Garcia-Mena, V (Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA, 2021)
The FAO and the OMS have warned on the high risk to health from the consumption of fried food due to their high energy density (fats) which leads to obesity, heart problems and the development of toxic compounds, like acrylamide, produced in frying oils. Chile has high obesity indices in adults, who affect 25.1% of the population. A fundamental cause is the increasing consumption of trashed food, like fried potatoes as an inevitable component. This is due mainly to the fact that fats and carbohydrates activate areas of the brain related to pleasure, leading to addiction. In this paper deals with an extruded food product similar to fried potatoes in configuration and organoleptic characteristics; made with raw materials of low commercial value. This product is aimed at producing a food similar to fried potatoes, but with low oil absorption capacity during frying, allowing to offer a healthier alternative to the population. The oil absorption for the samples submitted in both extrusions, were lower than in the commercial product. This fact presents the challenge of obtaining a prototype that generates a lower absorption of oil, realizing the changes that are already glimpsed with the preliminary tests carried out. © 2021, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved.